Potential of AKR1B10 as a Biomarker and Therapeutic Target in Type 2 Leprosy Reaction - Soares, Cleverson T.; Fachin, Luciana R. V.; Trombone, Ana P. F.; Rosa, Patricia S.; Ghidella, Cássio C.; Belone, Andrea F. F. (Frontiers in Medicine, 2018)
Abstract The AKR1B10 (aldo-keto reductase family 1 member B10) gene has important functions in carcinogen-induced neoplasia. AKR1B10 is also expressed in type 2 reaction leprosy patients (R2). We measured the expression of AKR1B10 in the skin lesions of patients with leprosy by immunohistochemistry from biopsies that encompassed the spectrum of types of leprosy, based on the Ridley and Jopling classification (10 samples each of tuberculoid [TT], borderline tuberculoid [BT], mid-borderline [BB], and borderline lepromatous [BL] lesions; four samples of lepromatous lesions [LL]), reactional leprosy (14 samples of type 1 Reaction [R1] and 10 samples of type 2 Reaction [R2]), and biopsies from 9 healthy control (HC) subjects. In addition, 46 lepromatous lesions (BL and LL), 45 lepromatous lesions in regression, and 115 R2 lesions were included. Eight of 10 R2 samples (80%), 3 of 46 active BL and LL samples (6%), 23 of 45 BL and LL samples in regression (51%), and 107 of 115 R2 samples (93%) were positive for AKR1B10, differing significantly between all groups (p < 0.05). AKR1B10 expression was highest in the cytoplasm of macrophages. Thus, AKR1B10 is overexpressed on the lepromatous side (BL and LL) in samples that are in regression, especially type 2 reaction-associated lesions, rendering it a potential marker of type 2 reactional episodes of leprosy and a target of drugs against reactional episodes.